Analysis of The Final Exam of Odd Semester Grades in Arabic for Fifth Grade Students of MI Kebomlati Tuban / Taḥlīl Bunūd Al Ikhtibār Al Nihā’i Limādati Al Lugah Al Arabiyah Fi Al Madrasah Al Ibtidā’iyah Al Islāmiyah Kebomlati Tūban - Reni Lailina Hidayah; Saadatud Darain; Ahmad Zainun Yusuf; Nur Qomari; Faisal Mahmoud Adam Ibrahim (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
The purpose of this study was to analyze the final grade assessment items in the odd semester of Arabic for fifth-grade students at MI Kebomlati Tuban for the 2020/2021 academic year. This study uses a quantitative approach. The data in this study were obtained through question sheet documents and answers to the fifth-grade students of MI Kebomlati Tuban and were analyzed using formulas according to classical test theory (CTT) by using test validity based on the difference in power, the level of difficulty, and the question fraud. The results of this study are: (1) the results of the different power test show that there are 2 items with very good quality of difference, 19 good items, 7 medium items and 7 other items that do not have different power, even 1 of them has a value negative. So that the 7 items cannot be used; (2) at the level of difficulty, 9 items were found in the